2019
DOI: 10.3390/jof5020028
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans and non-albicans Isolates from Bloodstream Have Different Capacities to Induce Neutrophil Extracellular Traps

Abstract: Neutrophils activated with pathogens or their products induce formation of extracellular traps (NETs), but if this constitutes a general response against all pathogenic species in a single genus or intrageneric differences exist remains unknown, yet this is of great importance for the establishment of effective treatments. To determine this, we analyzed neutrophil extracellular traps formation after the stimulation with bloodstream isolates from different Candida species (Candida albicans, C. tropicalis, C. pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…2c), measurements of nuclear area of SYTOX-positive objects performed with ImageJ were used to quantify NETs release. NETs were defined as SYTOX-positive events of area larger than 100 μm 2 , assuming that nuclear area of unstimulated granulocyte is ~ 80 μm 2 [ 21 , 22 ]. Subsequently, the number of SYTOX-positive events of area > 100 μm 2 was divided by the total number of cells, as manually counted in bright field images.…”
Section: Methodsmentioning
confidence: 99%
“…2c), measurements of nuclear area of SYTOX-positive objects performed with ImageJ were used to quantify NETs release. NETs were defined as SYTOX-positive events of area larger than 100 μm 2 , assuming that nuclear area of unstimulated granulocyte is ~ 80 μm 2 [ 21 , 22 ]. Subsequently, the number of SYTOX-positive events of area > 100 μm 2 was divided by the total number of cells, as manually counted in bright field images.…”
Section: Methodsmentioning
confidence: 99%
“…Neutrophil extracellular traps (NETs) are networks of extracellular fibers composed of modified chromatin decorated with specific cytoplasmic and granular proteins that entrap and eliminate bacteria, fungi, parasites, and viruses, are one of the infection defense mechanisms of neutrophils. Recently, it was reported that C. glabrata in some clinical isolates did not show NETs formation, which may be correlated with the high mortality rates in infected patients [16]. C. tropicalis is capable of adhesion with C. albicans and a dual culture biofilm of C. albicans with C. tropicalis offers a growth advantage for C. tropicalis [17].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found strains of Candida spp. that produced phospholipases could induce NETosis, while C. glabrata did not (Campos-Garcia et al, 2019). Since this research did not control other variables between Candida spp., the role of phospholipases in NETosis needs further investigation.…”
Section: Candida Albicansmentioning
confidence: 91%
“…This work was supported by the CAMS Innovation Fund for Medical Science (2017-I2M-1-017), the National Natural Science Foundation of China (81773338), and the Nanjing (Zawrotniak et al, 2019;Urban et al, 2006;Urban et al, 2009;Metzler et al, 2011;Byrd et al, 2013;Romao et al, 2015;Gabrielli et al, 2016;Kenno et al, 2016;Gogol et al, 2016;Johnson et al, 2016;Kenny et al, 2017;Zawrotniak et al, 2017;Wu et al, 2017;Guiducci et al, 2018;Padder et al, 2018;Khandagale et al, 2018;Hoyer et al, 2018;Wu et al, 2019;Campos-Garcia et al, 2019;Negoro et al, 2020;Kasperkiewicz et al, 2020;Thiam et al, 2020;Shankar et al, 2020;Kernien et al, 2020;Smolarz et al, 2021;Afonso et al, 2021;Sprenkeler et al, 2022)…”
Section: Fundingmentioning
confidence: 99%